Korea's Move to e-Procurement - Cho, Junghun; Byeon, Hee Seok (World Bank, Washington, DC, 2012)
In 1997 the Korean government began reforming its notoriously complicated, nontransparent, corrupt public procurement system, introducing e-procurement to exploit the country's well-developed information and communications infrastructure. Through extensive business process reengineering and information strategy planning, the Public Procurement Service-the agency formerly responsible for buying government goods and services-has been transformed into a one-stop information center. E-procurement has generated numerous benefits, including: Enhanced transparency and public trust-by reducing contacts between officials and suppliers and by sharing information between government agencies and the public. Increased managerial efficiency-by achieving economies of scale in procurement, with an estimated $2.5 billion a year in savings from the $26 million investment. This note analyzes how Korea achieved these outcomes, the lessons of its experience, and the challenges that remain for its e-procurement system.